Optimizing Healthcare Services at Suwawa Health Center through Android-based Information System - Muliati Badaruddin; m salim; Santawali (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
Healthcare services are the implementation of efforts to maintain optimal health levels, both at the individual and community levels. Improving the quality of healthcare services in Community Health Centers (Puskesmas) has become increasingly important, especially since people today are more discerning in choosing the healthcare services they receive. The research objective is to design and implement an information system that facilitates service transformation at Puskesmas Suwawa. This system aims to enhance the accessibility of healthcare services by allowing the public to undergo health check-ups, report complaints, and consult with general practitioners without the need to physically visit the Puskesmas. The research method used is the research and development method, which aims to create a specific product and test its effectiveness. The system was tested using Whitebox testing, where the registration web module was converted into a flowchart, and Cyclomatic Complexity (CC) was calculated, as well as Blackbox testing. The test results showed that Cyclomatic Complexity (CC) was 6, and the V(G) test result was 6. Based on these results, it can be concluded that the Android-based healthcare service information system at Puskesmas Suwawa, Bone Bolango Regency, can improve the effectiveness and efficiency of providing healthcare services to the public